2021
DOI: 10.18662/rrem/13.1sup1/397
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety and Student Resilience in the Context of School Assessment

Abstract: Countless studies have shown that there is a connection between anxiety felt during exams and school performance. We as individuals are exposed to failure in the moment of an exam and for those who are not familiar with the context, the opportunity to fail is more probable to happen. The goals of this study are: to identify the relation between exam anxiety and scholar resilience based on gender of the subject and the class he is a part of. The sample of the study was formed of 96 students from IV grade. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Regarding those studies’ attempts to explain the relationship between assessment and resilience, Berg and Pietrasz [ 60 ] used experiential classroom exercises (competitive activities) to help students develop resilience. Similarly, Clipa et al [ 16 ] found that students’ resilience increases when they practice formative assessment, which reduces test anxiety. Although both studies have the same findings, the intervention proposed in the current study was developed based on a solid evidence-based framework [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding those studies’ attempts to explain the relationship between assessment and resilience, Berg and Pietrasz [ 60 ] used experiential classroom exercises (competitive activities) to help students develop resilience. Similarly, Clipa et al [ 16 ] found that students’ resilience increases when they practice formative assessment, which reduces test anxiety. Although both studies have the same findings, the intervention proposed in the current study was developed based on a solid evidence-based framework [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has become vital to seek comprehensive approaches that incorporate both individual and systemic (organizational) factors [ 4 , 5 ]. With the expansion of resilience research, medical educators are increasingly interested in identifying interventions that foster resilience among medical students [ 3 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In situations where pressure is active and good performance matters, people can become so anxious that they are not actually able to give their best. When children have the skills and knowledge to do very well in these situations, their excessive anxiety affects their school performance (Clipa et al, 2021). A little nervousness can be helpful, making you feel mentally alert and ready to take on the exam's challenges.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the formative assessment that is continuous and used to obtain information and improve children's performance and training. Formative assessment methods used in kindergarten include observation, portfolios, self-reflection and peer reflection, questions and answers, discussions, and testing sheets (Clipa et al, 2021;Hartman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%